User-intervened structured meshing methods and applications for complex flow fields based on multiblock partitioning. Issue 1 (17th November 2020) - Cai, Wen-Hao; Zhan, Jie-Min; Luo, Ying-Ying
Abstract: Recently, a series of automatic structured grid generation methods for different fields or specific problems have been proposed by various researchers, but these methods still have some disadvantages or limitations. Therefore, in the present study, several user-intervened structured meshing methods for complex flow fields have been introduced for multiblock docking and multiblock splicing based on multiblock structured grid technology. Besides, three applications compared with the other methods or experiments are discussed to illustrate the crucial workflow of the user-intervened partitioning. The successful implementation of these partitioning examples demonstrates the feasibility and effectiveness of the methods described herein. And the techniques and criteria summarized in the present paper are quite practical and helpful for high-quality meshing. Graphical Abstract: